The Effectiveness of Theological Education in Ukraine: A Research Project - Ferenczi, Jason (Bogoslovskie razmyšlenija, 2006)
Research Project "Theological Education in Ukraine" is designated primarily for the leaders and faculties of theological schools. But it could be an interesting and helpful tool for leadership of the local churches and church unions. Beside of that those, who are interested in theological education and training new ministers for the churches, will find the data for their own research projects. This article is the special journal version of the project edition which is shorter then a book edition. But it still includes the history, premise, methods, area of the research and the results. The research was conducted in several leading theological schools in Ukraine. The authors of the project were looking for the answers for the most important questions in theological education - how the theological training meets the needs of the churches and the society, what are the factors lead to high quality of the training and what are the stumbling blocks in that way? The article includes not only the observational data, but some conclusions and recommendations.